The Role of Abraham Kuyper's Cultural Mandate in Christian Religious Education - Majesty, Gilbert Timothy; Juaniva Sidharta (International Journal of Christian Education and Philosophical Inquiry, 2025)
This research aims to analyze the role of Abraham Kuyper's cultural mandate in the context of Christian Religious Education. Abraham Kuyper, a Dutch theologian and statesman, emphasized the importance of the cultural mandate as an integral part of the Christian faith, where believers are called to transform all aspects of life, including education, according to the principles of the Kingdom of God. This research uses a qualitative method with a theological-philosophical analysis approach to Kuyper's thought and its relevance to CRE. The research findings indicate that Kuyper's cultural mandate provides a strong theological foundation for CRE, emphasizing the integration of faith, science, and daily life. The concept of sphere sovereignty proposed by Kuyper also promotes a holistic approach in Christian Religious Education), where education focuses not only on spiritual aspects but also on the development of character, ethics, and social responsibility. Additionally, this study found that the implementation of the cultural mandate in CRE can strengthen Christian identity amidst pluralism and secularization. The implication of these findings is the importance of a CRE curriculum based on the Kuyperian vision, which emphasizes cultural transformation through education. This research contributes to the development of CRE that is relevant and contextual in addressing the challenges of the times.